UMPSAs Jelajah Prihatin to assess needs of prospective students - Naqiah, Puaad (UMPSA, 2024)
KELANTAN, 20 September 2024 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) is welcoming new students in need as part of an initiative to facilitate their registration on 28 September. UMPSA remains attentive to the needs of students from the time they register until graduation, focusing particularly on their welfare throughout their studies.